Sudut Pandang Berbeda Masalah Zakat Dan Shalat Dari Prespektif Pemuka Agama - Nur Fadhillah Eka Putri; Syarifuddin Syarifuddin; Emillia Susanti; Syafni Defila Arinta; Siti Dela Yanti (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This journal contains the relationship between Pancasila and religion, as well as the perspectivs of religious leaders. This journal was created with the aim of explaining how the relationship between Pancasila and religion and how we understand the different perspectives between each human being, explaining the nature of Pancasila, how to apply Pancasila in community life, which articles contain the relationship between Pancasila and religion and how we can respect each other between religious communities in Indonesia, understand more deeply about Prayer and Zakat contained in the Pillars of Islam which are obligatory for every Muslim, by collecting and analyzing data obtained from direct debates through videos, articles that discuss this problem.